2020
DOI: 10.3390/ani10040652
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Underfed Twin-Bearing Ewes with Herbal Vitamins C and E: Impacts on Birth Weight, Postnatal Growth, and Pre-Weaning Survival of the Lambs

Abstract: Simple Summary: In twin-bearing ewes, undernourishment during pregnancy lowers the birth weight and increases morbidity and mortality of lambs. One of the causes is oxidative stress, which can be prevented by supplementing antioxidant vitamins. In the present study we tested the effect of supplementation with herbal vitamins C and E alone or in combination with concentrate on pregnancy outcomes and growth and survival of lambs during early postnatal stages (lactation). The results showed that vitamin supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
5
13
0
Order By: Relevance
“…We recently showed that antioxidant supplementation during the entire gestation period in naturally undernourished ewes kept in Chilean Patagonia counteracted oxidative stress and increased fetal weight near lambing (day 140 of gestation; length of gestation = 148 days) in both single and twin pregnancies [ 18 ]. Furthermore, in a very recent study carried out in our undernourished twin pregnancy model in which the effects of nutritional supplementation (to cover the requirements of pregnancy) and antioxidant supplementation were compared, we found that both types of supplementation significantly improved the lamb birth weight [ 19 ]. In the present pilot study, we aim to contribute to the knowledge of the course of such effects, evaluating the redox status of twin fetuses and verifying whether the effects of nutritional and antioxidant supplementation are already evident at the end of the second term of gestation before starting the accelerated fetal growth.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that antioxidant supplementation during the entire gestation period in naturally undernourished ewes kept in Chilean Patagonia counteracted oxidative stress and increased fetal weight near lambing (day 140 of gestation; length of gestation = 148 days) in both single and twin pregnancies [ 18 ]. Furthermore, in a very recent study carried out in our undernourished twin pregnancy model in which the effects of nutritional supplementation (to cover the requirements of pregnancy) and antioxidant supplementation were compared, we found that both types of supplementation significantly improved the lamb birth weight [ 19 ]. In the present pilot study, we aim to contribute to the knowledge of the course of such effects, evaluating the redox status of twin fetuses and verifying whether the effects of nutritional and antioxidant supplementation are already evident at the end of the second term of gestation before starting the accelerated fetal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, previous studies in sheep with twin pregnancies have shown that maternal oral supplementation with antioxidant vitamins C and E during pregnancy increases these vitamins in the cord blood of near-to-term fetuses, diminishing their oxidative stress and increasing their body weight [ 19 ]. Afterwards, the lambs from supplemented ewes have increased plasma antioxidant capacity and higher body weight at birth, improved survival during the lactation period, and showed a trend towards higher body weight at weaning [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 million babies are born premature every year and they need special care just to stay alive [11]. During gestational period, the maternal oral intake of vitamin E increases the weight of foetus [12]. The oral administration of vitamin E was given to children to combat malabsorption disorders.…”
Section: Introductionmentioning
confidence: 99%